TRANSPARANSI PEMERINTAH DESA DALAM PENYELENGGARAAN PEMERINTAH: Studi Di Desa Bawan Kecamatan Banama Tingang Kabupaten Pulang Pisau - Ester Sonya Ulfaritha Lapalu; Andrius Dewantara (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2022)
This study aims to determine: 1) to know the implementation of the principle of transparency, in the Bawan village government in Banama Tingang district Pulang Pisau, 2) to find out the factors that influence the implementation of the principle of transparency in the administration of the Bawan village government in the Banama Tingang sub-district Pulang Pisau. Transparency of governance in the Bawan village through the community’s right to access information is still not optimal because access to information provided to the Bawan village community is still not able to be reached or accessed quickly by the community. Supporting factors: to support transparency in the administration of government in the village, starting from the leadership element, in this case, the village head. The village head of Bawan always provides good support to all employees who carry out their duties well so that the process of implementing transparency in the village of Bawan can run well. Inhibiting factor: In every government administration of course there are obstacles / or obstacles to be faced, as is the case with the Bawan village starting from the budget shortage factor so that there are still many government programs that have not been implemented.